The Role of miR-21 in Osteoblasts–Osteoclasts Coupling In Vitro - Agnieszka Smieszek; Klaudia Marcinkowska; Ariadna Pielok; Mateusz Sikora; Lukas Valihrach; Krzysztof Marycz (Cells, 2020)
MiR-21 is being gradually more and more recognized as a molecule regulating bone tissue homeostasis. However, its function is not fully understood due to the dual role of miR-21 on bone-forming and bone-resorbing cells. In this study, we investigated the impact of miR-21 inhibition on pre-osteoblastic cells differentiation and paracrine signaling towards pre-osteoclasts using indirect co-culture model of mouse pre-osteoblast (MC3T3) and pre-osteoclast (4B12) cell lines. The inhibition of miR-21 in MC3T3 cells (MC3T3inh21) modulated expression of genes encoding osteogenic markers including collagen type I (Coll-1), osteocalcin (Ocl), osteopontin (Opn), and runt-related transcription factor 2 (Runx-2). Inhibition of miR-21 in osteogenic cultures of MC3T3 also inflected the synthesis of OPN protein which is essential for proper mineralization of extracellular matrix (ECM) and anchoring osteoclasts to the bones. Furthermore, it was shown that in osteoblasts miR-21 regulates expression of factors that are vital for survival of pre-osteoclast, such as receptor activator of nuclear factor κB ligand (RANKL). The pre-osteoclast cultured with MC3T3inh21 cells was characterized by lowered expression of several markers associated with osteoclasts’ differentiation, foremost tartrate-resistant acid phosphatase (Trap) but also receptor activator of nuclear factor-κB ligand (Rank), cathepsin K (Ctsk), carbonic anhydrase II (CaII), and matrix metalloproteinase (Mmp-9). Collectively, our data indicate that the inhibition of miR-21 in MC3T3 cells impairs the differentiation and ECM mineralization as well as influences paracrine signaling leading to decreased viability of pre-osteoclasts.